PENDIDIKAN DAN MOBILITAS SOSIAL DI KABUPATEN SOPPENG - Luktfy Alam,; Syamsu A Kamaruddin; A. Octamaya Tenri Awaru (JURNAL PENDIDIKAN IPS, 2025)
In modern life, education and social mobility are often seen as two interrelated entities, both of which are influenced by aspects of social change and local traditions and wisdom that prevail in a region. This study aims to analyze how education and social mobility are viewed by the community in Soppeng Regency where these phenomena continue to experience dynamics and contextualization in society. This study uses a qualitative approach with the In-Depth Interview technique with various parties, such as students, parents, teachers, and community leaders, to gain insight into how education in Soppeng Regency is in relation to their opportunities to move socially and economically. The analysis was carried out by grouping information based on themes or patterns that emerged from the results of interviews with informants. The results of the study show that the soppeng community views that education is a very important thing in the process of social movement or mobility, education can not only provide skills and improve competence or educational expertise can also develop character and sharpen wisdom which are all part of the occurrence of social mobility in the soppeng community. This research has a great impact on how we view education and social mobility as something dynamic due to social change. The results of this research will provide implications and messages on how we as a society must be wiser and wiser in looking at education and social mobility in an increasingly complex society.